PEMBERIAN PROTEIN ADHESIN 38-KILODALTON MYCOBACTERIUM TUBERCULOSIS PERORAL MENINGKATKAN JUMLAH MAKROFAG DAN LIMFOSIT USUS MENCIT BALB/c - Rahma Triliana; Ade A Kartosen; Dianika P Puspitasari; Sri Murwani; Sanarto Santoso; Maimun Z Arthamin (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (M.tb), is one of the world health problems. Oral vaccination of M.tb hasa potential to reduce the risk and complication of TB. The 38-kDa adhesin protein as one of oral TB vaccine candidates has not beenproven. This study is aimed to determine M.tb 38-kDa adhesin protein effect on macrophage and lymphocyte numbers in mice intestineafter an oral administration. BALB/c mice (n=20), age 6–8 weeks, and were divided into 4 groups: control (K), adjuvant (A), 38-kDa100μg adhesin protein (P), and combination of 100μg 38-kDa adhesin protein with adjuvant (PA). An oral administration was givenat the beginning with 2 boosters every 4 weeks. After 3 days of the second booster, the mice were killed and the intestine was taken andstained with haematoxylin eosin (HE) to measure its macrophages and lymphocytes number. The mean ±2SD were 18.4 (3.71) and6.09 (0.34), 23.0 (7.78) and 8.86 (1.19), 42.2 (13.63) and 23.49 (3.91), 95.4 (30.11), and 53.57 (13.79) respectively for K, A, Pand PA group. The statistical test showed a significant difference among each group revealing the role of M.tb 38-kDa adhesin proteinas immunogenic inducing cellular immunity in intestine. In this study, so far it was found that the oral administration of M. tb 38-kDaadhesin protein has an ability to increase macrophage and lymphocyte numbers in the mice intestinal BALB/c.